A Hypothetical Comparison between Event Marketing and Conventional Advertising - Ara, Husna; Sarwar, Nafish; Zabeen, Mashruha (Universiti Sains Malaysia, 2014)
The contemporary marketers all over the world are shifting their centre of attention into event marketing due to its intense reputation as a mode of promotion. However, the efficiency of event marketing as a promotional tool over the common advertising practices is yet to be measured. Hence, this article provides a hypothetical analysis via a two-sample proportionate test to measure the effectiveness of event marketing over the usual marketing promotion. The result evidently exhibits that; event marketing is relatively more effective mode of promotion compared to other conventional methods of advertising for developing goodwill, building customer-company relationship and ensuring further re-purchasing tendency.